Dust exposure and the impact on hospital readmission of farming and wood industry workers for asthma and chronic obstructive pulmonary disease (COPD) - Vested, Anne; Kolstad, Henrik A; Basinas, Ioannis; Burdorf, Alex; Elholm, Grethe; Heederik, Dick; Jacobsen, Gitte H; Kromhout, Hans; Omland, Øyvind; Schaumburg, Inger; Sigsgaard, Torben; Vestergaard, Jesper Medom; et al. (Scandinavian Journal of Work, Environment & Health, 2021)
' ' OBJECTIVES ': 'It is still not well established how occupational air pollutants affect the prognosis of asthma or chronic obstructive pulmonary disease (COPD). This study uses nationwide Danish registers and quantitative dust industry exposure matrices (IEM) for the farming and wood industries to estimate whether previous year dust exposure level impacts hospital readmissions for workers diagnosed with asthma or COPD. ' ' METHODS ': 'We identified all individuals with a first diagnosis of either asthma (769 individuals) or COPD (342 individuals) between 1997 and 2007 and followed them until the next hospital admission for asthma or COPD, emigration, death or 31 December 2007. We included only individuals who worked in either the wood or farming industries at least one year during follow-up. We used logistic regression analysis to investigate associations between dust exposure level in the previous year and hospital readmission, adjusting for sex, age, time since first diagnosis, socioeconomic status, and labor force participation. ' ' RESULTS ': 'Asthma readmissions for individuals with low and high dust exposure were increased [adjusted rate ratio (RRadj) 2.52, 95% confidence interval (CI) 1.45–4.40] and RRadj 2.64 (95% CI 1.52–4.60), respectively. For COPD readmission, the risk estimates were RRadj 1.36 (95% CI 0.57–3.23) for low and RRadj 1.20 (95% CI 0.49–2.95) for high exposure level in the previous year. For asthma readmission, stratified analyses by type of dust exposure during follow-up showed increased risks for both wood dust [RRadj 2.67 (95% CI 1.35–5.26) high exposure level] and farming dust [RRadj 3.59 (95% CI 1.11–11.59) high exposure level]. No clear associations were seen for COPD readmissions. ' ' CONCLUSIONS ': 'This study indicates that exposure to wood or farm dust in the previous year increases the risk of hospital readmission for individuals with asthma but not for those with COPD.
Keywords: air pollutant; asthma; chronic obstructive pulmonary disease; COPD; dust exposure; exposure; farmer; farming; hospital readmission; industry exposure matrix; lung disease; wood industry; woodworker